Performance of young male swimmers in the 100-Meters front crawl - de Mello Vitor, F.; Silveira Böhme, M. T. (Pediatric Exercise Science, 2010)
Youth swimming performance may be influenced by anthropometric, physiology and technical factors. The present paper examined the role of these factors in performance of 100m freestyle in swimmers 12-14 years of age (n = 24). Multiple regression analysis (forward method) was used to examine the variance of the 100 meters front crawl. Anaerobic power, swimming index and critical speed explained 88% (p < .05) of the variance in the average speed of 100 meters front crawl among young male pubertal swimmers. To conclude, performance of young swimmers in the 100 meters front crawl is determined predominantly by physiological factors and swimming technique.